Determining the immunological characteristics of a novel human monoclonal antibody developed against staphylococcal enterotoxin B. Issue 7 (2nd July 2020) - Liu, Yuanyuan; Song, Zhen; Ge, Shuang; Zhang, Jinyong; Xu, Limin; Yang, Feng; Lu, Dongshui; Luo, Ping; Gu, Jiang; Zou, Quanming; Zeng, Hao
ABSTRACT: Staphylococci are the main cause of nosocomial infections globally. The exotoxin staphylococcal enterotoxin B (SEB) produced by methicillin-resistant Staphylococcus aureus is a major cause of pathology after a staphylococcal infection. We previously isolated an anti-SEB human monoclonal antibody designated as M0313. Here we further characterize this antibody in vitro and in vivo. Immunoblotting analysis and ELISA results indicated that M0313 accurately recognized and bound to SEB. Its binding affinity to native SEB was measured at the low nM level. M0313 effectively inhibited SEB from inducing mouse splenic lymphocyte and human peripheral blood mononuclear cell proliferation and cytokine release in cell culture. M0313 also neutralized SEB toxicity in BALB/c female mice. Most importantly, M0313 promoted the survival of mice treated with SEB-expressing bacteria. In-vivo imaging revealed that M0313 treatment significantly reduced the replication of SEB-expressing bacteria in mice. The neutralization capacity of M0313 correlated with its ability to block SEB from binding to major histocompatibility complex II and T-cell receptor by binding to the SEB residues 85–102 and 90–92. Thus, the monoclonal antibody M0313 may be developed into a therapeutic agent.